Cover Picture: Ultralow Cost Electrochemical Sensor Made of Potato Starch and Carbon Black Nanoballs to Detect Tetracycline in Waters and Milk (Electroanalysis 9/2018). Issue 9 (7th September 2018) - Delgado, Karina P.; Raymundo‐Pereira, Paulo A.; Campos, Anderson M.; Oliveira, Osvaldo N.; Janegitz, Bruno C.
Abstract : The cover picture illustrates detection of the antibiotic tetracycline in tap water, river water, milk samples and in solutions prepared with commercial tablets of this medicine using an ultralow cost (<US$ 0.005 per unit of sensing layer) electrochemical sensor made of potato starch (PS) and carbon black (CB) deposited on a glassy carbon electrode (GCE). The high performance was attributed to the enhanced conductivity and large surface area by incorporating carbon black into potato starch. More details are discussed in the article by Karina P. Delgado, Paulo A. Raymundo Pereira, Anderson M. Campos, Osvaldo N. Oliveira Jr. and Bruno C. Janegitz. DOI:10.1002/elan.201800294